2010
DOI: 10.1353/csd.0.0109
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Self-Efficacy on Academic Success of First-Generation College Sophomore Students

Abstract: The purpose of this study was to analyze the effects of self-efficacy on academic success of first-generation college sophomore students. The participants in the study consisted of college sophomores from 5 of the 23 California State University campuses. An online College Self-Efficacy Inventory was employed to measure participants’ self-efficacy levels. The study explored four areas: the relationship between self-efficacy scores and academic success as defined by GPA and persistence rates, the academic succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
124
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(140 citation statements)
references
References 16 publications
11
124
3
2
Order By: Relevance
“…Some studies have reported significant differences in self-efficacy between male and female students' (Vogt, Hocevar, & Hagedorn, 2007;Sakiz, 2011&Vuong, Brown-Welty, & Tracz, 2010. For example, Lent et al (2005) and Vogt, Hocevar, & Hagedorn (2007) have reported that male students have significantly higher self-efficacy than females.…”
Section: The Difference Between Male and Female Students In Self-effimentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported significant differences in self-efficacy between male and female students' (Vogt, Hocevar, & Hagedorn, 2007;Sakiz, 2011&Vuong, Brown-Welty, & Tracz, 2010. For example, Lent et al (2005) and Vogt, Hocevar, & Hagedorn (2007) have reported that male students have significantly higher self-efficacy than females.…”
Section: The Difference Between Male and Female Students In Self-effimentioning
confidence: 99%
“…For example, (Sakiz, 2011;Vuong, Brown-Welty, & Tracz, 2010;Nasiriyan, Khezri Azar, Noruzy, & Dalvand, 2011) have found that self-efficacy had a significant and positive effect on academic achievement. Britner & Pajares (2006) also found that self-efficacy was best predictor of physics conceptual understanding as well as physics grade.…”
Section: Introductionmentioning
confidence: 99%
“…Results of a meta-analytic study showed that self-efficacy beliefs were positively related to students' academic attainment and persistence attitudes across a wide variety of fields (Multon, Brown & Lent, 1991). More recent studies also have reported a positive relation of college self-efficacy to students' college satisfaction, academic performance and expectations of persistence to graduation (DeWitz, Woolsey, & Walsh, 2002;Garriott, Hudyma, Keene & Santiago, 2015;Vuong, Brown-Welty, Tracz, 2010) including students of Hispanic descent (Gloria, Castellanos, Lopez, & Rosales, 2005;Ojeda, Flores, & Navarro 2011;Torres & Solberg, 2001). …”
Section: Self-efficacymentioning
confidence: 99%
“…Kord (2008) stresses the possible positive and negative influence of online social networking on college students' academic experiences, and which will continue to offer more traditional support to students through a less traditional medium (Heyman, 2010). The interaction with faculty and social networking with peers are important factors for academic success (Vuong, Brown-Welty, & Tracz, 2010). If students are kept engaged in their academic programs (Dizik, 2010), this elicits students' stronger positive opinions for e-learning environments (Lei & Gupta, 2010;Riffell & Sibley, 2005).…”
Section: Relationship Of Social and Academic Integration External Atmentioning
confidence: 99%